Regional cell specific RNA expression profiling of FACS isolated Drosophila intestinal cell populations - Dutta, Devanjali; Buchon, Nicolas; Xiang, Jinyi; Edgar, Bruce (Current protocols in stem cell biology, 2015)
The adult Drosophila midgut is built of five distinct cell types, including stem cells, enteroblasts, enterocytes, enteroendocrine cells, and visceral muscles, and is divided into five major regions (R1 to R5), which are morphologically and functionally distinct from each other. This unit describes a protocol for the isolation of Drosophila intestinal cell populations for the purpose of cell type-specific transcriptome profiling from the five different regions. A method to select a cell type of interest labeled with green or yellow fluorescent protein (GFP, YFP) by making use of the GAL4-UAS bipartite system and fluorescent-activated cell sorting (FACS) is presented. Total RNA is isolated from the sorted cells of each region, and linear RNA amplification is used to obtain sufficient amounts of high-quality RNA for analysis by microarray, RT-PCR, or RNA sequencing. This method will be useful for quantitative transcriptome comparison across intestinal cell types in the different regions under normal and various experimental conditions. © 2015 by John Wiley & Sons, Inc.
Gesehen am 02.07.2020